2023
DOI: 10.1093/jas/skad008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age at first calving on performance traits in Irish beef herds

Abstract: Reducing age at first calving has been a challenge in beef herds. There is anecdotal evidence that herd owners choose to calve heifers older because of the perceived consequences of calving heifers at 24 mo of age compare to 36 mo on performance traits in beef herds. The objective of this study was to estimate the association of calving heifers at younger ages on subsequent performance traits, calving interval, longevity, cow weight, dystocia and progeny weaning weight for parities 1 to 5. Available to the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Tarrés et al (2004) observed that the optimal age for first calving to promote a long productive life was between 30 and 33 months in the Bruna dels Pirineus beef breed. Some beef producers may also choose to delay the breeding of young heifers because of the anecdotal perception that there is a higher risk of calving difficulty and potential negative consequences on lifetime performance of cows that calve at a younger age (Twomey & Cromie, 2023). They observed that cows that calved at younger ages were more likely to require assistance at their first parturition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tarrés et al (2004) observed that the optimal age for first calving to promote a long productive life was between 30 and 33 months in the Bruna dels Pirineus beef breed. Some beef producers may also choose to delay the breeding of young heifers because of the anecdotal perception that there is a higher risk of calving difficulty and potential negative consequences on lifetime performance of cows that calve at a younger age (Twomey & Cromie, 2023). They observed that cows that calved at younger ages were more likely to require assistance at their first parturition.…”
Section: Resultsmentioning
confidence: 99%
“…They observed that cows that calved at younger ages were more likely to require assistance at their first parturition. However, Twomey and Cromie (2023) claimed that this negative consequence could be negated by good management and breeding decisions. They also found that younger calving cows weaned lighter calves for their first three lactations and themselves weighed less for their first four lactations.…”
Section: Resultsmentioning
confidence: 99%
“…Найбільший ризик вибракування спостерігався у первісток, малих стад і низькопродуктивних корів (Ghavi Hossein-Zadeh, 2016). Крім того, найнижчий ризик вибракування був виявлений для корів, які отелилися в наймолодшому віці (<27 місяців), а корови з віком першого отелення >33 місяців мали найбільший ризик (Twomey & Cromie, 2023).…”
Section: вступunclassified
“…The age at first calving is determined by genetics factors and the management of farms. Twomey et al (2023) observed that reducing age at first calving to 24 months is efficient for beef cattle breeds. Brzakova et al (2020) reported that to improve the production of beef cattle is necessary to reduce unproductive periods of females by reducing age at first calving.…”
Section: Introductionmentioning
confidence: 99%